2005
DOI: 10.3168/jds.s0022-0302(05)72711-9
|View full text |Cite
|
Sign up to set email alerts
|

Flavor and Stability of Pasteurized Milk with Elevated Levels of Conjugated Linoleic Acid and Vaccenic Acid

Abstract: The objectives of this study were to determine if flavor differences between 2% fat pasteurized milks with and without naturally enhanced vaccenic acid (VA) and cis-9, trans-11 conjugated linoleic acids (CLA) levels could be detected over the commercial shelf life of the product and to determine if milk with elevated VA and cis-9, trans-11 CLA levels was more susceptible to development of light-induced oxidative flavor defects. Cows were fed a control diet or the same ration supplemented with 2% soybean oil an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 25 publications
3
30
0
3
Order By: Relevance
“…In line with other research that evaluated acceptability or sensory characteristics of FA-modified milk Ramaswamy et al, 2001;Kitessa et al, 2004;Lynch et al, 2005), we found that our modified milk had no effect on the mean overall liking, liking of specific modalities, or purchase intent ratings across our consumer population (n = 115). Our trained sensory panel observed some differences in sensory attributes between both modified and control samples and the commercial comparators.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In line with other research that evaluated acceptability or sensory characteristics of FA-modified milk Ramaswamy et al, 2001;Kitessa et al, 2004;Lynch et al, 2005), we found that our modified milk had no effect on the mean overall liking, liking of specific modalities, or purchase intent ratings across our consumer population (n = 115). Our trained sensory panel observed some differences in sensory attributes between both modified and control samples and the commercial comparators.…”
Section: Discussionsupporting
confidence: 72%
“…Some studies have highlighted that FA composition may alter the textural profile of cheese (Palmquist et al, 1993;Chilliard and Ferlay, 2004;Jones et al, 2005;Givens and Shingfield, 2006). Conversely, other studies have shown no effect of PUFA supplementation of the ruminant diet, which predominantly incorporated fish oil, on the sensory characteristics of milk Ramaswamy et al, 2001;Kitessa et al, 2004;Lynch et al, 2005), cheese (Jones et al, 2005;VargasBello-Pérez et al, 2015), or butter ). More research is needed to examine the acceptability of milk and dairy products produced from ruminants that have been subjected to a period of oleic acid-rich supplementation.…”
Section: Introductionmentioning
confidence: 99%
“…Supplementing diets with oils, crushed seeds or rumen-protected lipids is a common nutritional means for manipulating milk fatty acid composition [12] despite forages often being the major source of fatty acids in the diet [23]. On the other hand, ruminant ingestion of plant oils rich in linoleic acid, including soybean oil [34] and sunflower oil [27], has increased milk fat CLA concentrations effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Jones et al [31] confirm these findings. Lynch et al [51] exposed pasteurised milk rich in CLA (4.74 g·100 g -1 fatty acids) to light. There was no effect of light exposure on fatty acid composition initially or over a 14-d storage period.…”
Section: Shelf-life Stability and Special Effects Of Processingmentioning
confidence: 99%